Aboriginal Students and School Mobility in British Columbia Public Schools - Aman, Cheryl (Alberta Journal of Educational Research, 2008)
In British Columbia, K-12 school Aboriginal students’ completion rates are far from equivalent to those of their non-Aboriginal peers. In addition, there is a high degree of variability in Aboriginal students’ school completion rates across schools and communities. Administrative data associating approximately 1.5 million school census records of students enrolled in public schools province-wide over 13 years were examined. A longitudinal cohort design was employed to examine individual-level and school-level differences in the school completion outcomes of Aboriginal students. Findings indicate that school change, or student mobility, of secondary Aboriginal students was a prevalent feature in Aboriginal high school trajectories. A negative relationship exists between the frequency of school change during the high school years and Aboriginal students’ school completion.